BRIDGING THE GAP: A SYSTEMATIC REVIEW OF BARIATRIC SURGERY'S EFFECTS ON CARDIAC HEALTH - Dr Muhammad Haider Ali; Dr Sania Malik; Dr Muhammad Jawad Zahid; Dr Mashhood Alam Khan; Dr Muhammad Saleem; Dr Shabeer ahmad; Dr Muhammad Waqas; Dr Hamza Khan Toru; Dr Aftab Faheem; Dr Aisha Farooq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: This study compares preoperative and post-operative cardiac imaging measures to examine the effects of bariatric surgery on heart shape and function in obese patients.Methodology: Using PubMed, MedLine, Ovid, and Cinhal, this work searched the literature for bariatric, metabolic, weight loss, and obesity surgery as well as echocardiography, MRI, cardiac imaging, cardiac dimensions, & ventricular dimensions. Studies included had an initial follow-up of three months and reported on heart structural and function parameters obtained by MRI or echocardiography. Study excluded had conflicting or no preoperative or postoperative data. The Newcastle-Ottawa scale was used for quality assessment; PRISMA guidelines were followed for statistical analysis, which computed and pooled results using a model of random effects with 95% confidence intervals, weighted mean differences, and DerSimonian & Laird modelling. We looked at inter-study heterogeneity with the I2 statistic.Results: Bariatric surgery greatly improves a number of cardiac indices, including left atrium diameter (1.967 mm, 95% CI 0.980-2.954), left ventricular end-diastolic volume (13.28 ml, 95% CI 5.22-21.34 ml), as well as left ventricular mass index (11.2, 95% confidence intervals (CI) 8.2-14.1%). Positive increases were noted for the left ventricular ejection fraction (1.198, 95% CI 0.050-2.347) and the E/A ratio (0.189, 95% CI 0.113–0.265).Conclusion: In obese patients, bariatric surgery has been shown to have beneficial impacts on diastolic function, systolic function, and cardiac structure. The alteration of the enteric cardiac axis may be a contributing factor to these outcomes. However, future research endeavours should prioritize the acquisition of more robust evidence to precisely determine the most effective bariatric procedures for preventing and treating a diverse spectrum of obesity-related cardiac pathologies, in addition to further developing strategies for managing obesity cardiomyopathy.